2021
DOI: 10.3390/nu13113832
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories and Determinants of Physical Activity during COVID-19 Pandemic: A Population-Based Study of Middle-Aged and Elderly Individuals in The Netherlands

Abstract: Physical inactivity is a major public health problem, and there are concerns this might have increased during the COVID-19 pandemic. We aimed to identify distinct trajectories of physical activity over a 6-week period after the first restrictive measures and to explore determinants of these trajectories in a population-based cohort of middle-aged and elderly in the Netherlands (n = 5777). We observed that at least 59% of participants did not meet the World Health Organization recommendations for physical activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
(45 reference statements)
0
4
0
3
Order By: Relevance
“…In a study from the Netherlands (N = 5777), as many as 59% did not meet World Health Organization criteria for physical activity during COVID-19 (Hofman et al, 2021). In this study there was a steadily low trajectory based on latent class trajectory analysis of three different time points.…”
Section: Inactivitymentioning
confidence: 53%
“…In a study from the Netherlands (N = 5777), as many as 59% did not meet World Health Organization criteria for physical activity during COVID-19 (Hofman et al, 2021). In this study there was a steadily low trajectory based on latent class trajectory analysis of three different time points.…”
Section: Inactivitymentioning
confidence: 53%
“…They identified a range of factors associated with different trajectories, such as age, gender, education, income, employment status, and health [ 101 ]. In a study of a cohort of 5777 middle-aged or elderly adults in the Netherlands, Hofman et al (2021) [ 102 ] likewise identified a number of sociodemographic determinants of various trajectories of physical activity after the introduction of restrictive measures, including older age, poor educational status, and retirement status.…”
Section: Review Resultsmentioning
confidence: 99%
“…Em relação ao método de coleta de dados, foram realizadas entrevistas por telefone (n= 4; 16%); pesquisas realizadas por meio de questionários online (n= 4; 16%); por meio de questionários enviados por correio (n= 5; 20%); combinação entre entrevista por telefone ou pesquisas por meio de questionários online ou por correio (n= 1; 4%); combinação apenas entre pesquisas por meio de questionários online ou por correio (n= 1; 4%); entrevista presenciais acrescidas da realização de avaliação clínica (n= 2; 8%); apenas avaliação clínica (n= 3; 12%); por fim, alguns estudos não relataram a forma que os questionários foram enviados para os participantes da amostra (n= 5; 20%). Para que fosse possível realizar a análise das condições clínicas e pessoais dos participantes, em relação aos impactos físicos decorrentes da COVID-19, foram utilizadas as seguintes escalas, seja de forma individual ou conjunta: Índice de Qualidade do Sono de Pittsburgh (Chiara Stival et al, 2022;); Questionário COVID-19 da coorte LifeLines (Amy Hofman et al, 2021); Kihon Checklist -KCL (Satake et al, 2021;Kawamura et al, 2021;Yamada et al, 2020;Yamada et al, 2021); Questionário Nutricional Simplificado de Apetite -SNAQ (Satake et al, 2021;); Questionário do Estudo de Avaliação do Espaço de Vida da Universidade do Alabama em Birmingham (Portegijs et al, 2021;Leppa et al, 2021); questionário de Atividade Física de Yale para idosos (Portegijs et al, 2021;Leppa et al, 2021); Escala de alfabetização em saúde (Shiratsuchi et al, 2021); Índice de triagem de fragilidade (Shiratsuchi et al, 2021); Índice de Barthel -BI (Kawamura et al, 2021;Fernández-García et al, 2021;Pérez et al, 2021); Índice de Atividades de Frenchay -FAI (Kawamura et al, 2021); Subescala Impacto na Participação e Questionário de Autonomia -IPA (Leppa et al, 2021); Questionário Internacional de Atividade Física -IPAQ (Yamada et al, 2020;Carriedo et al, 2020;Yamada et al, 2021;Murukesu et al, 2021;Sasaki et al, 2021;Lee et al, 2021); Escala de Alfabetização Crítica em Saúde -CCHL (Yamada et al, 2020); Índice de Competência do Instituto Metropolitano de Gerontologia...…”
Section: Resultsunclassified
“…Essa circunstância pode ser explicada pelo fato de as medidas restritivas não terem mudado nos Países Baixos durante o período de realização do estudo, fato que não se aplica ao restante do mundo. Na Holanda, os idosos podiam sair, mesmo que por tempo limitado, para realizar atividade física durante a pandemia (Hofman et al, 2021). Apesar disso, as medidas restritivas puderam afetar a saúde física no que se refere à diminuição de passos diários dos idosos.…”
Section: Discussionunclassified
See 1 more Smart Citation